p38β and Cancer: The Beginning of the Road - Olga Roche (International Journal of Molecular Sciences, 2020)
The p38 mitogen-activated protein kinase (MAPK) signaling pathway is implicated in cancer biology and has been widely studied over the past two decades as a potential therapeutic target. Most of the biological and pathological implications of p38MAPK signaling are often associated with p38α (MAPK14). Recently, several members of the p38 family, including p38γ and p38δ, have been shown to play a crucial role in several pathologies including cancer. However, the specific role of p38β (MAPK11) in cancer is still elusive, and further investigation is needed. Here, we summarize what is currently known about the role of p38β in different types of tumors and its putative implication in cancer therapy. All evidence suggests that p38β might be a key player in cancer development, and could be an important therapeutic target in several pathologies, including cancer.